Prove the following :
$$\sqrt{rr_1r_2r_3}$$ = S

Solution

We know, $$r=\cfrac { S }{ s } ,{ r }_{ 1 }=\cfrac { S }{ s-a } ,{ r }_{ 2 }=\cfrac { S }{ s-b } ,{ r }_{ 3 }=\cfrac { S }{ s-c } $$
$$\Longrightarrow r{ r }_{ 1 }{ r }_{ 2 }{ r }_{ 3 }\cdot \cfrac { { S }^{ 4 } }{ s(s-a)(s-b)(s-c) } =\cfrac { { S }^{ 4 } }{ { S }^{ 2 } } ={ S }^{ 2 }\\ \therefore \sqrt { r{ r }_{ 1 }{ r }_{ 2 }{ r }_{ 3 } } =S$$
Now, $$\cot { \cfrac { A }{ 2 }  } =\sqrt { \cfrac { s(s-a) }{ (s-b)(s-c) }  } ;\cot { \cfrac { B }{ 2 }  } =\sqrt { \cfrac { s(s-b) }{ (s-a)(s-c) }  } ;\cot { \cfrac { C }{ 2 }  } =\sqrt { \cfrac { s(s-c) }{ (s-a)(s-b) }  } $$
Now, $$\cot { \cfrac { A }{ 2 }  } \cot { \cfrac { B }{ 2 }  } \cot { \cfrac { C }{ 2 }  } =\sqrt { \cfrac { { s }^{ 2 }\cdot s(s-a)(s-b)(s-c) }{ { \left( s-a \right)  }^{ 2 }{ \left( s-b \right)  }^{ 2 }{ \left( s-c \right)  }^{ 2 } }  } =r^{2} \cdot \cfrac { s }{ (s-a)(s-b)(s-c) } \cdot S \\=\cfrac{S^{2}}{s^{2}}\cdot \cfrac{s}{(s-a)(s-b)(s-c)} \cdot S$$
$$=\cfrac { s(s-a)(s-b)(s-c) }{ { s }^{ 2 } } \cdot \cfrac { s }{ (s-a)(s-b)(s-c) } \cdot S=S$$